CHARACTERISTICS OF SOME OLIVE VARIETIES DURING GROWTH AND MATURITY - S.R. Al-Obady (Mesopotamia Journal of Agriculture)
Three varieties of olives (Bashike, Manzanillo and Dugal) were used to study the chemical and physical changes during growth and maturity (From July to November). The results showed that moisture % of Bashike, Manzanillo and Dugal varieties were significantly (P> 0.05) increased . The highest percentage was noticed during October , and started to decrease in November. The percentages of ash, protein, carbohydrate, and crude fiber significantly (P > 0.05 ) decreased , while the pectin contents were significantly (P > 0.05) increased . The highest percentages of pectin was noticed in August, then decreased toward the end of the growth period, also a slight decrease in total acidity, whereas pH values increased during the growth period. The contents of chlorophyll a and b significantly (P> 0.05) decreased at the end of the growth period. The physical properties of the olive fruits were also changed during the growth period. Length of the fruits, diameter, volume, weight and flesh/ seed were significantly (P> 0.05) increased, whereas the hardness and density significantly (P> 0.05) decreased with at the end of the growth period.